دور التحليل الائتماني في ضمان تسديد القروض وفوائدها في البنوك التجارية اليمنية: دراسة على البنوك العاملة في حضرموت - لرضي، حمزة عبدالحكيم (جامعة البيضاء, 2022)
تهدف الدراسة إلى التعرف على الدور الذي يلعبه التحليل الائتماني في ضمان تسديد القروض وفوائدها في البنوك التجارية اليمنية، وكذا الوقوف على المعوقات والصعوبات التي تواجه البنوك التجارية في حل مشكلات تسديد القروض وفوائدها، وتقديم مجموعة من التوصيات والمقترحات التي من الممكن أن تسهم في رفع كفاءة البنوك في تحصيل قروضها. ومن أجل تحقيق أهداف الدراسة تم تصميم استمارة استبيان وجهت إلى أفراد عينة الدراسة من مديري وموظفي إدارات الائتمان والاستثمار ذوي العلاقة المباشرة في اتخاذ قرارات منح الائتمان المصرفي، وتم تحليل البيانات من خلال استخدام أسلوب التحليل الإحصائي SPSS وقد توصلت الدراسة إلى أن إدارة التسهيلات الائتمانية في البنوك التجارية اليمنية لا تتخذ قرارات بمنح التسهيلات الائتمانية بصورة عشوائية؛ وإنما تعتمد على مجموعة من المؤشرات، مثل: المؤشرات المالية، والمحاسبية، والتسويقية، والاقتصادية والأخرى، ويمكن القول إنه إذا كان قرار إعطاء القروض للعملاء ينطوي على درجة من المخاطرة، فإن إدارة القروض باعتمادها على هذه المجموعة من المؤشرات تعمل على تقييم أهلية العملاء للحصول على القروض وتحديد قدرتهم على سداد القروض. The role of credit analysis in ensuring repayment of loans, and interest in Yemeni Commercial Banks. The study aims to identify the role played by the credit analysis to ensure repayment of loans, and benefits in the Yemeni Commercial Banks, as well as the standing on obstacles and difficulties which faced the commercial banks in resolving a set of recommendations and suggestions which contribute to rise the efficiency of banks in the procurement of loans In order to achieve the aims of the study, questioner has designed to declaim study participants consisting of managers, officers of credit department's, and investment. Who has a relationship of making decisions with granting of credit bank, and analysis the data through using a method of statistical analysis SPSS. The study reaches in to a series of results: The credit facilities management in Yemeni Commercial Banks doesn't make decision in granting of credit facilities by a randomly way. But it depends on a set of indications, such as financial, accounting, marketing, economic, and others. It can be said that, if the decision of giving loans to the customers involving a degree of risk the loan administration's by depending on these series of indicators working on evaluate the clients eligibility to get loans, and determine their ability to repay them.
Keywords: القطاع المصرفي -- البنوك التجارية -- الائتمان المصرفي -- التسهيلات الائتمانية -- اليمن